THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE, TRANSACTIONAL AND JOB SATISFACTION ON THE PERFORMANCE OF TEACHERS OF SMA NEGERI 1 MAKMUR - Arifin, A Hadi; Marbawi, Marbawi; Heikal, Mohd; Afrina, Mutia (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to determine the effect of transformational leadership style, transactional leadership style and job satisfaction on the performance of SMA Negeri 1 Makmur teachers. This study uses primary data obtained by distributing questionnaires to 39 respondents. This study uses a quantitative and qualitative approach. The data analysis method used is multiple linear regression model with the help of SPSS. The results showed; Transformational leadership style has a negative and insignificant effect on teacher performance, while transactional leadership style and job satisfaction has a positive and significant effect on teacher performance.